KOMODITAS UNGGULAN KLUSTER AGROINDUSTRI PERKEBUNAN DI PROVINSI SUMATERA SELATAN - Hendrixon Hatta; Udisubakti Ciptomulyono (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2020)
The government in an effort to increase global competitiveness makes a plan through the RPJPN document (2005-2025) which implies a gradual transformation to develop a competitive economy in accordance with regional competencies and excellence. Thus, the challenges faced are efforts to increase competitiveness through the development and implementation of innovation systems (innovation driven economy). The national innovation system (SINAS) consists of the support of a number of regional innovation systems (SIDa) so that industrial clusters are formed based on the thematic superior regions. South Sumatra Province in the process of determining the plantation industry cluster based on regional superior commodities is based on the results of deliberations by the regional government without the support of an educational approach undertaken in the determination of the thematic superior. The determination of this industrial cluster can be used as a direction for regional development that can facilitate regional innovation actors in taking strategic policy steps in advancing the region. So this research aims to determine the regional superior commodities and products that are carried out with the academic draft approach to have acceptable and operational characteristics. In this study the determination of regional superior commodities and products is carried out with a scientific approach using the LQ, Integration DEMATEL and ANP methods. The results of this study are coffee (4.54), rubber (4.49) and oil palm (4.45) priority commodity-based priority products that have a good industrial value chain to be developed by innovation actors in formulating policies and programs for support the regional superior products in order to have national and global competitiveness.